INFORMATION SHARING IN OBOR PROJECTS TO ENSURE BETTER PERFORMANCE: MEDIATING ROLE OF DYNAMIC MANUFACTURING CAPABILITY - Thaiprayoon, Khajornsak; Sriyakul, Thanaporn; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2019)
Chinaâ??s One Belt One Road (OBOR) initiative has also connected Thailand with many other markets to support its manufacturing industry. Yet, due to such long-range trade relationships, information sharing is becoming a key figure for success. Such information sharing from manufacturer to customer reduces the uncertainties and can improve production process too. In this study, author has seen the impact of manufacturer to supplier information sharing and manufacturer to buyer information sharing on supply chain performance of such firms which are located in OBOR plans. Moreover, mediating role of dynamic manufacturing capability has also been tested in relationship between information sharing dimensions and supply chain performance. Data has been collected from those manufacturing firms of Thailand who are either doing or willing to do trade through OBOR initiative through survey questionnaire. Responses were then analyzed on SPSS and AMOS to get the empirical results. Findings have revealed that information sharing dimensions have significant impact on supply chain performance and dynamic manufacturing capability is playing a significant positive mediating role in the respective relationships. This study is novel due to the mediating role of dynamic capabilities which were not taken in prior literature and also has its very own implications for academia and practice.